2022
DOI: 10.1039/d2se00251e
|View full text |Cite
|
Sign up to set email alerts
|

Infiltration of nickel and copper catalysts into a GDC backbone assisted by supercritical CO2 for efficient SOFC anodes

Abstract: This study describes an original method developed for the shaping of composites Solid Oxide Fuel Cells (SOFC) anodes including either nickel or copper as metal. There are prepared by catalyst...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
4
1
Order By: Relevance
“…Even when compared to electrodes featuring high GDC composition, such as those incorporating nano-Ni particles on the GDC surface, 30 electrode C remains competitive. However, in comparison to the optimal results reported in the literature 21 for electrodes obtained by infiltrating Ni into the GDC matrix, electrode C falls short in terms of performance.…”
Section: Resultscontrasting
confidence: 62%
See 1 more Smart Citation
“…Even when compared to electrodes featuring high GDC composition, such as those incorporating nano-Ni particles on the GDC surface, 30 electrode C remains competitive. However, in comparison to the optimal results reported in the literature 21 for electrodes obtained by infiltrating Ni into the GDC matrix, electrode C falls short in terms of performance.…”
Section: Resultscontrasting
confidence: 62%
“…[18][19][20] The performance of cells resulting from the infiltration of GDC into a porous backbone of pure Ni reported in the literature 20 did not achieve as good results as those from the infiltration of Ni or Ni-ceria into metal-ceramics 14 or sintered oxide backbones. 21 Several studies have delved into the structural changes observed in commonly utilized Ni/GDC anodes. The primary aging phenomena are attributed to Ni coarsening, agglomeration, and depletion.…”
Section: List Of Symbolsmentioning
confidence: 99%
“…Infiltrating GDC into pure Ni anode improved the polarization resistance from 10.7 Ω•cm² to 1.50 Ω•cm² at 700 °C (18)(19)(20). The performance of cells from infiltration of GDC into a porous backbone of pure Ni reported in literature (20) did not achieve as good results as those from the infiltration of Ni/Niceria into metal-ceramics (14) or sintered oxide backbones (21).…”
Section: Introductionmentioning
confidence: 90%
“…With O 2− conduction in the solid phase, the SOFC runs at 800-1000 • C. A sandwiched structure anode/electrolyte/cathode with diverse materials is always used in traditional SOFCs [47][48][49][50][51]. Due to the varied electrode materials, traditional SOFCs require at least two heating stages, resulting in high cost and energy consumption.…”
Section: Types Of Fcsmentioning
confidence: 99%